2010
DOI: 10.1007/s11666-010-9500-5
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Spraying Coupled to Nano-Pulsed Nd-YaG Laser Surface Pre-treatment

Abstract: Cold-spraying coupled to nano-pulsedThe effect of Al2017 substrate pre-treatment using pulsed laser ablation on adhesion strength of coldsprayed Al coating is examined. A high energy pulsed laser beam was coupled with a cold-spray gun to result in laser ablation of the substrate surface a few milliseconds prior to the deposition. The influence of the laser fluence and repetition rate on substrate surface morphology and physico-chemical properties are investigated. Coating-substrate interfaces were observed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…TEM studies have shown that the native oxide film of the substrate is detected at the interface coating-substrate after the impact of the cold sprayed particles ( Ref 12,36). The oxide film is detected after the spraying at the interface coating-substrate but in these regions a weak adhesion is observed.…”
Section: Deposition Of Coldmentioning
confidence: 99%
“…TEM studies have shown that the native oxide film of the substrate is detected at the interface coating-substrate after the impact of the cold sprayed particles ( Ref 12,36). The oxide film is detected after the spraying at the interface coating-substrate but in these regions a weak adhesion is observed.…”
Section: Deposition Of Coldmentioning
confidence: 99%
“…For instance, Olakanmi et al, (Ref 14) and Christoulis et al, (Ref 15,16,17) demonstrated LACS as a pretreatment method in which the laser beam passes milliseconds prior to the cold spray jet for deposition. Consequently, the laser beam softens the deposition site and thus the sprayed particles impinge on the softened substrate thereby forming a coating that is bonded to the substrate.…”
Section: Historical Developments Of Lacs and Process Descriptionmentioning
confidence: 99%
“…In another configuration (figure 8), a pulsed Nd-YAG laser was coupled with the cold-spray gun to result in the laser beam passing milliseconds prior to the cold-spray jet for deposition, (Christoulis et al, 2009;Christoulis et al 2010). Pulsed Nd-YAG laser were operated only during the first pass in order to clean the substrate surface.…”
Section: Laser-assisted Cold Spray (Lacs)mentioning
confidence: 99%